Effect of the time of shoot topping on the architecture of the bunches and the temporal dynamics of Botrytis bunch rot (Botrytis cinerea) in the 'Sauvignon Blanc' grapevine (Revista de Ciências Agroveterinárias, 2024)
Shoot topping is a management method in the search for a vegetative and productive balance in the grapevine. However, there is little information about its effect on the architecture of the bunches and on the occurrence of Botrytis bunch rot. In this context, the aim of this study was to evaluate the effect of different shoot topping times on cluster architecture and the temporal dynamics of Botrytis bunch rot in 'Sauvignon Blanc' grapevines. The work was carried out in the 2016/2017 harvest, in a commercial vineyard located in the municipality of São Joaquim. The treatments consisted of the management of the shoot topping, removing approximately 50 cm from the apical portion of the branches at different phenological stages: plants without shoot (control), separate inflorescence, full bloom, pea-sized berries and veráison. Bunch architecture and the temporal dynamics of Botrytis bunch rot were evaluated. The shoot topping the 'Sauvignon Blanc' grapevine did not influence the architecture of the bunches, regardless of the phenological stage at which it was carried out. About Botrytis bunch rot, there was no effect for the different shoot topping times on the onset of symptoms, time to reach maximum incidence and time to reach maximum severity, as well as for the disease incidence and severity variables, although there was an effect on the AUDIPC and AUDSPC areas, with the highest values being observed in the full bloom phenological stage for AUDIPC and in the veraison for AUDSPC. Therefore, it is recommended to carry it out on the pea berry.
Keywords: Vitis vinifera L.; green pruning; high-altitude wines; grapevine diseases